2020
DOI: 10.18325/jkmr.2020.30.3.23
|View full text |Cite
|
Sign up to set email alerts
|

The Preclinical Study of Hyeolbuchugeo-tang (Xuefuzhuyu-tang) on Bone Healing in Rats with Rib Fracture

Abstract: Objectives The purpose of this study is to evaluate the healing effect of Hyeolbuchugeotang (HC) in rats with rib fracture. Methods Rats were randomly divided into 5 groups (naive, control, positive control, HC-L and HC-H). All groups except naive group were subjected to bone fracture of rib. Naive group received no treatment at all. Control group was fed with phosphate buffered saline. Positive control group was orally medicated with tramadol. Experimental group was orally medicated with HC extract (50 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Previous experimental studies on herbal medicine showed that callus formation occurred faster in the herbal medicine group than in the control group. [ 37 , 38 ] Measurement of radical scavenging activity of herbal extracts showed a dose-dependent increase in antioxidant activity and a significant decrease in the production of the inflammatory mediator interleukin-1β, indicating that herbal extracts can help relieve inflammatory responses accompanying fractures. [ 39 , 40 ] Osteogenesis during the reparative phase can be facilitated by bone morphogenetic protein type 2 that mediates the differentiation of osteoblasts and activates transforming growth factor-β1 and Sox9 that regulates the transcription of type 2 collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies on herbal medicine showed that callus formation occurred faster in the herbal medicine group than in the control group. [ 37 , 38 ] Measurement of radical scavenging activity of herbal extracts showed a dose-dependent increase in antioxidant activity and a significant decrease in the production of the inflammatory mediator interleukin-1β, indicating that herbal extracts can help relieve inflammatory responses accompanying fractures. [ 39 , 40 ] Osteogenesis during the reparative phase can be facilitated by bone morphogenetic protein type 2 that mediates the differentiation of osteoblasts and activates transforming growth factor-β1 and Sox9 that regulates the transcription of type 2 collagen.…”
Section: Discussionmentioning
confidence: 99%
“…현재까지 골절 치료를 위한 다방면의 한약 연구가 보 고되었다. 방제를 활용한 연구로는 加味芎歸湯 33) , 加味 身痛逐瘀湯 14,15) , 順氣活血湯 16) , 復元活血湯 17,18) , 當歸鬚 散 19,20) , 破血散疼湯 21) , 血府逐瘀湯 22) , 桃紅四物湯…”
Section: 고찰»»»unclassified
“…한의학 서적 중《外臺秘要》에서는 "救急療救骨折, 接 令如故"로 골절에 대한 병명을 처음 언급하였고 7) , ≪醫 宗金鑑≫에서는 부위별 보호대를 활용하는 방법을 제시 하였으며 8) , ≪聖濟總錄≫에서는 골절치료에 한약을 초 기에는 活血祛瘀, 중기에는 接骨續筋, 후기에는 補氣養 血, 健壯筋骨 하는 시기별 방법을 설명하였다 9) . 요 구성 약재로 쓰였을 뿐만 아니라 13) , 골절 유합에 효과 적임을 보고한 복합약물연구 加味身痛逐瘀湯 14,15) , 順氣活 血湯 16) , 復元活血湯 17,18) , 當歸鬚散 19,20) , 破血散疼湯 21) , 血府 逐瘀湯 22) , 桃紅四物湯 23) 를 이용하여 5 mm 간격으로 단순 결찰 봉합하였다. 반 대쪽 다리도 같은 방법으로 골절을 유발하였다(Fig.…”
unclassified